2012
DOI: 10.1016/j.pec.2012.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Decision preparation, satisfaction and regret in a multi-center sample of men with newly diagnosed localized prostate cancer

Abstract: Objective To describe relationships between use of the Personal Patient Profile-Prostate (P3P) decision support system and patient characteristics, and perceived preparation for decision making (PrepDM), satisfaction and decisional regret in the context of prostate cancer treatment choice. Methods 494 men with localized prostate cancer (LPC) were randomized to receive the P3P intervention or usual care and completed pre-treatment, 1-month and 6-month outcome measures. Multivariable linear regression models w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 27 publications
4
78
1
Order By: Relevance
“…In cancer care, much is known about the characteristics of newly diagnosed patients who do or do not seek information about their care, the topics about which they seek information, and the means they prefer for receiving that information [5][6][7][8] . In a recent population-based study, Nagler and colleagues 9 reported that the rate of information-seeking varied by tumour type: patients with colorectal cancer reported consistently less information-seeking than did patients with breast or prostate cancer, and the differences were most pronounced in patients with early-stage disease.…”
Section: Introductionmentioning
confidence: 99%
“…In cancer care, much is known about the characteristics of newly diagnosed patients who do or do not seek information about their care, the topics about which they seek information, and the means they prefer for receiving that information [5][6][7][8] . In a recent population-based study, Nagler and colleagues 9 reported that the rate of information-seeking varied by tumour type: patients with colorectal cancer reported consistently less information-seeking than did patients with breast or prostate cancer, and the differences were most pronounced in patients with early-stage disease.…”
Section: Introductionmentioning
confidence: 99%
“…In the largest randomized controlled trial evaluating the use of the P3P dma in American men, use of the aid did not predict decision regret 52 . Conversely, in a smaller randomized controlled trial in Scotland, investigators did find lower regret scores 6 months after treatment in the group that used the dma compared with a control group that did not 53 .…”
Section: Effectivenessmentioning
confidence: 85%
“…Equity indicators also feature prominently, with access to expertise and variations in outcomes between metropolitan versus regional patients and public versus private patients considered important when assessing quality and consistency-of-care. Studies have shown that patient-centred care is important in decision preparation, satisfaction and regret, by using appropriate language and formats for communication, fully preparing patients for tests and treatments and meeting the patients' needs for involvement in decisionmaking [27][28][29]. A review of patient decision making for localised prostate cancer found that the physician's recommendation plays a significant role in influencing the patient's choice of management and that most men will select the first treatment recommended to them.…”
Section: Discussionmentioning
confidence: 99%